Summary Report: Innovative Qualitative Approaches for CIS Monitoring and Evaluation - Carr, Edward R.; Onzere, Sheila N.; Goble, Rob (2019)
Climate information services (CIS) for agriculture and development are useful only when farmers have the ability to make changes in their activities and practices based on the information received. This ability is mediated by a wide range of factors and considerations, such as access to appropriate seeds or needed agricultural equipment, or the authority to make decisions about the cultivation of a particular farm plot. Different users of a CIS will have different abilities to act on weather and climate information, and therefore effective CIS design begins with the empirical identification of potential CIS users and their climate information needs as shaped by these mediating factors. At the same time, user expectations of CIS, environmental conditions, and the social and economic factors that shape the utilization of weather and climate information can change during the implementation of a project. To effectively monitor and evaluate CIS therefore requires approaches to monitoring and evaluation (M&E) that identify and analyze these complex factors. This report outlines lessons about CIS monitoring and evaluation drawn from two qualitative pilot assessments of CIS users and their needs in Senegal (Carr et al. 2018) and Rwanda (Onzere et al. 2018). These assessments were conducted by the Humanitarian Response and Development Lab (HURDL) as part of the Climate Information Services Research Initiative (CISRI) funded by the U.S. Agency for International Development. The goal of these assessments was to test innovative evaluation methodologies on ongoing programs to develop general lessons that could contribute toward improving the design and evaluation of CIS interventions. Specifically, HURDL tested the utility of the Livelihoods as Intimate Government (LIG) approach (described below) as a means of identifying different users and the factors that shape their different weather and climate information needs, for the Multidisciplinary Working Group (MWG) model in Senegal and the Climate Services for Agriculture Initiative (CSAI) in Rwanda. A growing literature demonstrates that understanding who the potential users of these CIS are, and their needs for weather and climate information, allows for the design of monitoring and evaluation efforts that are aimed at likely impacts. Further, because the potential impacts of climate information are never evenly distributed across a population, better understanding users and their information needs, calibrates monitoring and evaluation to what a significant impact looks like in a particular place or population.